2020
DOI: 10.1111/cpr.12899
|View full text |Cite
|
Sign up to set email alerts
|

RpS13 controls the homeostasis of germline stem cell niche through Rho1‐mediated signals in the Drosophila testis

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 50 publications
(118 reference statements)
0
9
0
Order By: Relevance
“…To further explore the roles of CG6015 during germline differentiation, we analyzed morphological changes of fusomes using immunofluorescence staining. Fluorescence tomography imaging has shown that fusomes, which are connections and special structures among germ cells, undergo dynamic changes from a punctate to a branched morphology during germline differentiation 30 , 31 . In this study, we observed that undifferentiated germ cells, which were marked by DNA and Vasa, accumulated in Bam> CG6015 RNAi testes (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To further explore the roles of CG6015 during germline differentiation, we analyzed morphological changes of fusomes using immunofluorescence staining. Fluorescence tomography imaging has shown that fusomes, which are connections and special structures among germ cells, undergo dynamic changes from a punctate to a branched morphology during germline differentiation 30 , 31 . In this study, we observed that undifferentiated germ cells, which were marked by DNA and Vasa, accumulated in Bam> CG6015 RNAi testes (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We next investigated the maintenance of cyst cells using cyst cell markers (Zfh1 and Eya) under conditions of loss of CG6015 in spermatogonia. In control testes, Zfh1 could label cyst stem cells (CySCs) and the early stage of cyst cells, while Eya was the marker of mature cyst cells 31 , 33 . The decay of Zfh1 is necessary for promoting the differentiation of cyst cell lineage 33 .…”
Section: Resultsmentioning
confidence: 99%
“…In Drosophila testes, the stem cell niche is studied as a model to mimic the formation of TGCTs. Drosophila provides a powerful genetically tractable system to study how germ cell differentiation has adapted in response to changes in external signals in testes [ 41 43 ]. Our study investigated roles of translation initiation factor eIF5 in Drosophila testes systemically and uncovered that CySC lineage eIF5 was essential for cyst cell differentiation, which then promoted germ cell differentiation via non-autonomous cell effects (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that CySC lineage cells lacking small ribosomal subunits, e.g., ribosomal protein S13 (RpS13), ribosomal protein S26 (RpS26), ribosomal protein S30 (RpS30), ribosomal protein S15Aa (RpS15Aa), and ribosomal protein S15Ab (RpS15Ab), lead to the accumulation of undifferentiated GSC-like masses [ 14 , 43 ]. In this study, we found that cyst cells lacking eIF5, eIF1A, and eIF2γ, which are key components of the pre-initiation complex, mimicked the phenotype of cells lacking several small ribosomal subunits for germ cell differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Immuno uorescence assays were conducted as previous descriptions 17,18,19,20 . Brie y, the slides containing target cells and tissues were incubated with primary and Alexa-Fluor secondary antibodies (Thermo Scienti c, Waltham, USA) orderly.…”
Section: Immuno Uorescencementioning
confidence: 99%